2017
DOI: 10.1108/pr-12-2015-0312
|View full text |Cite
|
Sign up to set email alerts
|

The job embeddedness-turnover relationship

Abstract: Purpose The purpose of this paper is threefold: first, to examine the job embeddedness (JE)-turnover intentions relationship in large and small organisations; second, to investigate how employee perceptions of each dimension of JE may differ in large and small organisations; and third, to determine if work group cohesion moderates the JE-turnover intentions relationship. Design/methodology/approach Using a short form of the original JE questionnaire, data were collected from 549 employees in organisations lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Studies on talent management have indicated that an organisation that is able to retain its human capital has a significant advantage over its competitors. This suggests that investing in mechanisms that can promote JE is crucial for organisational success because JE is known to predict turnover intention (Holtom & Darabi, 2018;Coetzer, Inma, & Poisat, 2017). As emphasised earlier, JE is characterised by three elements, that is, personal links with the organisation and people within the organisation; a sense of congruence between personal attributes and the demands of the job; and finally, a reluctance to lose the relationships and resources that have been established within or because of the organisation (Mitchell et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Studies on talent management have indicated that an organisation that is able to retain its human capital has a significant advantage over its competitors. This suggests that investing in mechanisms that can promote JE is crucial for organisational success because JE is known to predict turnover intention (Holtom & Darabi, 2018;Coetzer, Inma, & Poisat, 2017). As emphasised earlier, JE is characterised by three elements, that is, personal links with the organisation and people within the organisation; a sense of congruence between personal attributes and the demands of the job; and finally, a reluctance to lose the relationships and resources that have been established within or because of the organisation (Mitchell et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For social cohesion, quantitative measures related to networks, such as the strength of the tie between the focal actor and the other actors, or the tie strength between all actors, are useful [112]. Qualitatively, item scales assessing the perception of participants on interdependence issues leading to social cohesion will be valuable [113]. Finally, integrative negotiation could be operationalized quantitatively by coding integrative negotiation outcomes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Externally, fit applies to the community and how an individual feels connected to his or her community. Job embeddedness increases when employees' abilities and professional interests are matched with their organization and when they believe they fit in the community (Coetzer et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study conducted in South Africa examined the job embeddedness and turnover intention relationship in small and large organizations (Coetzer et al, 2017). Coetzer et al focused solely on the on-the-job links, sacrifice, and fit dimensions and did not include discussion of the off-the-job dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%